DECOLONIZATION OF THE HISTORY CURRICULUM IN INDIAN SENIOR SECONDARY SCHOOLS: AN ANALYSIS OF IMPLEMENTATION AT A HIGH SCHOOL IN CHENNAI - Uma.S (Satmata: Journal of Historical Education Studies, 2024)
This study aims to examine the practical implementation of a decolonized history curriculum in an Indian senior secondary school, with a case study conducted at Kendriya Vidyalaya in Chennai. While national education policies in India increasingly promote inclusive and postcolonial approaches to history teaching, there is limited empirical research on how these reforms are enacted in real classroom settings. Using a qualitative case study method, data were collected through classroom observations, semi-structured interviews with teachers and students, and analysis of curricular documents. The findings reveal a significant gap between policy discourse and pedagogical practice. Teachers express theoretical support for decolonizing the curriculum but face challenges such as rigid syllabi, exam-oriented instruction, and lack of professional development. Classroom practices largely remain textbook-centered, with minimal use of local histories, critical thinking tasks, or student-led inquiry. The study offers a novel contribution by linking national-level curriculum reforms with micro-level school dynamics, and by incorporating multiple data sources to highlight the nuanced realities of implementation. It also foregrounds the importance of teacher agency and contextual adaptation in achieving epistemic justice in postcolonial education. In conclusion, while efforts toward decolonization exist in rhetoric and curriculum content, their transformative potential remains underutilized without systemic support for pedagogical change. The research underscores the need for training, flexibility, and curricular autonomy to actualize meaningful historical education in India..